In vitro Bioactivities of Three Reputed Medicinal Plants of Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
The study was designed to evaluate the preliminary biological activities of crude methanol extracts of the leaf of Justicia gendarussa, Sansevieria trifasciata and Hydnocarpus kurzii and their organic soluble partitionates. The polyphenol content was determined spectrophotometrically and expressed as gallic acid equivalents. The total phenolic content was found to vary for different test samples ranging from 1.45 ± 0.25 mg to 40.73 ± 0.22 mg of GAE/ gm of dried extract. The antioxidant potential was evaluated by DPPH free radical scavenging assay using butylated hydroxytolune (BHT) and ascorbic acid as standards. In the assay, the CSF of H. kurzii and the PESF of J. gendarussa revealed the highest free radical scavenging activity with IC50 values 3.25 ± 0.05 ?g/ml and 24.68 ± 0.26 ?g/ml, respectively. The brine shrimp lethality bioassay was utilized to evaluate the cytotoxicity. The chloroform soluble fraction (CSF) and methanol extract (ME) of J. gendarussa exhibited strong cytotoxicity with LC50 values of 0.002 ?g/ml and 0.06 ?g/ml, respectively. The membrane stabilizing activity was assessed by evaluating hemolysis of RBC in hypotonic solution and was compared with acetyl salicylic acid. On the other hand, the chloroform soluble fraction of J. gendarussa and aqueous soluble materials of S. trifasciata produced 75.60% and 75.0% inhibition of hemolysis of RBC, respectively as compared to 77.9% inhibited by acetyl salicylic acid (0.10 mg/ml). DOI: http://dx.doi.org/10.3329/bpj.v17i2.22331 Bangladesh Pharmaceutical Journal 17(2): 147-150, 2014